Strains and stresses of three – layer composite bars and beams/Trisluoksnių kompozitinių strypų ir sijų deformacijos bei įtempimai - Bareišis, Jonas; Garuckas, Danas; Mikulskas, Alvydas A.; Striukienė, Danguolė (Journal of Civil Engineering and Management, 1997)
New composite anisotropic materials (CM) glass, carbon and boric plastics are more and more frequently used in engineering construction. By tuning strength and stiffness characteristics of CM under tension or bending with their density or price it is possible to get laminated construction of maximum strength and stiffness and minimum mass or price. The purpose of this work is to analyse regularity of distribution of stiffness or strains and stresses in three-layer bars, subjected to tension or bending by changing geometric characteristics of layer, materials and their position in cross-section of bars. The bar layers were formed of carbon plastic (A), hot (Sk) and cold hardening (Sc) glass plastics and epoxy resin (D). Equations were obtained describing the alteration of bar and beam stiffness and the alteration of normal stresses, all depending on relative thichness Ψ of bar or beam. The relative thickness Ψ is the ratio of middle layer height to the whole height. It has been shown that maximum stresses in exterior and middle layers (with elasticity modules E1 and E2accordingly) become equal when Ψ = E1 /E2 . The intensity of stiffness alteration depends on the magnitude of | E2 —E1 |. In the case of positive magnitude, the bar or beam stiffness increases while increasing Ψ. In the opposite case the stiffness decreases with decrease of Ψ. For the example of structure A-Sk—A and Ψ = 0,5, the price economy for 42% and mass reduction for 4% have been shown and compared with carbon plastic beam. Article in Lithuanian. First Published Online: 26 Jul 2012